Kajian Teologi Keluarga bagi Pemimpin Kristen dalam Kisah Abraham: Menelusuri Pola Inti Menuju Periferi - Asep Afaradi (Phronesis: Jurnal Teologi dan Misi, 2025)
The concept of Christian leadership often emphasises the character and competence of prominent biblical figures, while overlooking the foundational structures of sacred institutions from a Christian theological perspective. Furthermore, it frequently neglects essential supporting elements beyond these central individuals. This study explores the theology of the family as a lens through which to understand God's purposes for believers, while acknowledging that God's authority is manifested in every individual whom He appoints as a leader. Although leadership remains a central theme, this research focuses on the family narrative of Abraham which, when viewed from a New Testament Christian perspective, may not represent the ideal family model. Nevertheless, within Abraham’s story, the family emerges as the primary context through which God blesses His people and shapes leaders. The findings of this study suggest that Abraham’s family plays a pivotal role in forming his leadership and continues to offer valuable insights for the contemporary Church.